Assessing Portuguese Food Safety in Times of Crisis: an Empirical Analysis - Vale, S.; Ferreiro, Maria de Fátima (45th EBES Conference-Eurasia Business and Economics Society, 2023)
The Russia-Ukraine war impacted the world food system raising concerns about food security. Small countries such as Portugal, with a food trade balance deficit and energy dependency, suffered large increases in food prices that exposed their vulnerabilities and dependency on partners. This paper uses data analysis to evaluate Portuguese food security, focusing on the evolution of Portuguese self-sufficiency in agriculture and food trade balance in the XXI century in the context of its relations with the EU. The research allows the identification of the country’s international dependence on food supply and its vulnerability in a context of economic, geopolitical, and climatic risks. The Portuguese food system progressively increased its reliance on the EU members and is nowadays exposed to their weaknesses. From a political point of view, this study calls to attention the need to develop joint European policies to address the concern with food security in a region that is now irreversibly intertwined.